Left-Adjoined Bi-Valent Predicates in two Caribbean French-based creoles: Martinican and Haitian - Anne, Zribi-Hertz Belfrage; Jean-Louis, Loïc; Paul, Moles (Revista Letras, 2019)
This article presents a class of Serial Verb Constructions which includes the so-called ’take’ SVC-type and is shown to be productively attested in both Martinican (MQ) and Haitian (HC)—contrary to the information on these two creoles available in the APICS on-line atlas (Michaelis et al. 2013) and to a prediction made by Déchaine (1993) regarding HC. A comparative survey of MQ and HC data reveals that the construction under scrutiny has a broader extension in MQ than in HC. Although Déchaine’s (1993) approach to complex predicates provides us with a convenient formalism to represent the structure of this type of SVC, our descriptive results lead us to revise her theory in two important respects: (i) (French-based) Creole Tense systems cannot be regarded as incompatible with Left-Adjoined Bi-Valent Predicates; (ii) MQ evidence shows that the two components of Left-Adjoined Bi-Valent Predicates do not necessarily share the same external argument.